Cation-self-shielding strategy promises high-voltage all-Prussian-blue-based aqueous K-ion batteries - Qiubo Guo; Shuai Han; Yaxiang Lu; Ruijuan Xiao; Jin Li; Qingli Hao; Xiaohui Rong; Suting Weng; Yaoshen Niu; Feixiang Ding; Yang Yang; Hui Xia; et al. (Nature Communications)
Abstract Prussian blue analogues (PBAs) are promising electrode candidates for aqueous batteries because the inevitable interstitial water is generally thought to have little impact on battery performance. Currently, mounting researches have focused on optimizing PBA properties by varying transition metal composition, but less attention has been paid to interstitial water, especially in alkali metal-ion deficient PBAs with large cavities. Here, we employ the water-rich K0.01Mn[Cr(CN)6]0.74·4.75H2O as the negative electrode to study the effect of interstitial water. It is found that during de-potassiation, the electrode undergoes dehydration, which negatively impacts kinetics, distorts structure, and raises charging potential. A cation-self-shielding strategy involving Dihydroxyacetone (DHA) in the electrolyte to secure the water-rich state is then proposed. The built 1.82 V all-Prussian blue aqueous K-ion battery delivers a high practical specific energy of ~76 Wh kg−1 over 1.5 V (based on the total mass of active materials in both electrodes). This study reveals the significance of interstitial water on the kinetics of PBA negative electrodes and promotes the exploration of water-containing electrodes to develop high-voltage aqueous rechargeable batteries for energy storage applications.